THE REPRESENTATION OF SUICIDE IN THE SPANISH PRESS - Santos Diez, María Teresa (2020)
This article analyzes the treatment that the Spanish newspapers La Razón, El Mundo, El País and ABC gave to the subject of suicide from the 1st of January to the 31st of December of 2017. Through the methodology of content analysis, we have quantified the authorship of the texts, the genres and the information sources used. The conclusions indicate that news are basically descriptive and with little specialization and texts that dominate the negative and even sensational aspects. The main topics are consummated suicide, culture and attempted suicide. Suicide is also presented as a response or solution at the moment of facing problems.